Results from the NACC Uniform Data Set neuropsychological battery Crosswalk Study Running head: Neuropsychological Battery Crosswalk Study Results - Monsell, Sarah E. (Alzheimer Dis Assoc Disord, 2016)
INTRODUCTION: Four new nonproprietary tests were recommended for use in the National Alzheimer's Coordinating Center's Uniform Data Set Neuropsychological Battery. These tests are similar to previous tests but also allow for continuity of longitudinal data collection and wide dissemination among research collaborators. METHODS: A Crosswalk Study was conducted in early 2014 to assess the correlation between each set of new and previous tests. Tests with good correlation were equated using equipercentile equating. The resulting conversion tables allow scores on the new tests to be converted to equivalent scores on the previous tests. RESULTS: All pairs of tests had good correlation (ρ=0.68–0.78). Learning effects were detected for Logical Memory only. Confidence intervals were narrow at each point estimate, and prediction accuracy was high. DISCUSSION: The recommended new tests are well correlated with the previous tests. The equipercentile equating method produced conversion tables that provide a useful reference for clinicians and researchers.